Innovative surface modification of orthopaedic implants with positive effects on wettability and in vitro anti-corrosion performance. (September 2014) - Mozafari, M.; Salahinejad, E.; Sharifi-Asl, S.; Macdonald, D. D.; Vashaee, D.; Tayebi, L.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, sol–gel derived bioactive glass/zirconium titanate coatings were uniformly deposited on stainless steel orthopaedic implants, by using carboxymethyl cellulose as a particulate dispersant in the sol. The surface features, wetting, and in vitro electrochemical corrosion behaviour of the coated samples were evaluated. It was found that, by applying the coating on the substrate, the water contact angle was decreased, which is indicative of an improvement in the implant hydrophilicity. Also, the coating improved the corrosion resistance of the metallic implant, as realised by an increase in the corrosion potential and a decrease in the corrosion current density. Indeed, this coating acted as a physical protective barrier which retards the electrolyte access to the metal surface and thereby electrochemical processes.